1991
DOI: 10.1073/pnas.88.13.5685
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of immature thymocytes to thymic stromal cells through fibronectin molecules and its significance for the induction of thymocyte differentiation.

Abstract: Only 10-15% of unseparated thymocytes adhered to culture plates precoated with fibronectin (FN), but 60-70% of the CD4-8-(double-negative) thymocyte population did. This population bound to FN but not to collagen, laminin, or vitronectin. Its binding to FN was inhibited by anti-FN antibody or a mixture of synthetic peptides corresponding to two different sites of EN, termed the V10 sequence and the RGDS (Arg-Gly-Asp-Ser) sequence, which interact, respectively, with the VLA-4 and VLA-5 FN receptors expressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
1

Year Published

1992
1992
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(55 citation statements)
references
References 40 publications
(42 reference statements)
5
49
1
Order By: Relevance
“…Several laboratories including ours have shown that [31 integrins synergize with the TCR-CD3 pathway to promote T cell proliferation (4-6). [31 integrins are also reported to be involved in T or B cell differentiation through interaction with fibronectin expressed by stromal cells in thymus or bone marrow, respectively (7,8). Furthermore, it was also reported that integrin-ECM binding induced increases of cytoplasmic Ca 2+ and cytoplasmic pH (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories including ours have shown that [31 integrins synergize with the TCR-CD3 pathway to promote T cell proliferation (4-6). [31 integrins are also reported to be involved in T or B cell differentiation through interaction with fibronectin expressed by stromal cells in thymus or bone marrow, respectively (7,8). Furthermore, it was also reported that integrin-ECM binding induced increases of cytoplasmic Ca 2+ and cytoplasmic pH (9, 10).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of fibronectin on proliferation and differentiation of erythroid cells has been documented (75,76). Adhesion of CD4-CD8 -thymocytes to thymic stromal cells through FN-FN receptor interaction is known to be critical for their differentiation (77 Disruption ofnormal adhesion pathways between stem and stromal cells has been implicated as a critical factor in pathogenesis of chronic myeloid leukemia (81,82). Furthermore, after chemotherapy and/or total body irradiation, the observed extravascation of stem cells into peripheral blood (83) …”
Section: Resultsmentioning
confidence: 99%
“…Previously, in vitro systems have shown a requirement for integrins and integrin-related proteins for the maturation of CD4 Ϫ CD8 Ϫ to CD4 ϩ CD8 ϩ cells (12)(13)(14). Most of the in vitro data in mice point to the CD4 Ϫ CD8 Ϫ cells as being adhesive cells with activated integrins.…”
Section: Discussionmentioning
confidence: 99%
“…A number of in vitro studies have demonstrated that the engagement of integrins is required for the differentiation of CD4 Ϫ CD8 Ϫ cells to become CD4 ϩ CD8 ϩ cells (12)(13)(14). Furthermore, the Abmediated engagement of integrin receptors in addition to the engagement of the CD3 complex on CD4 ϩ CD8 ϩ thymocytes is required for cell proliferation in vitro (15,16).…”
Section: Integrin Functions Play a Key Role In The Differentiationmentioning
confidence: 99%